“Evaluación del cultivo de arroz (Oryza sativa L.) Iniap 1480 a la fertilización edáfica con Complefol azul y Novatec premium, en la zona de Babahoyo.”. - Miranda Acurio, Johnn Enrique (2018)
VII. SUMMARY The present experimental work takes place in the lands of the Palmar Experimental Farm of the Technical University of Babahoyo, located at Km 12 of the Babahoyo - Montalvo highway, between the geographic coordinates of 672 879 UTM of West longitude and 9797 144 UTM of South latitude. ; with a height of 8 m.s.n.m.The zone presents a humid tropical climate, with an average annual temperature of 25.60 °C; an annual rainfall of 2329.8 mm; relative humidity 82% and 998.2 hours of annual average heliophany. The soil has a flat topography, a loamy clay texture and regular drainage. As seed material rice seeds of the Iniap FL 1480 variety were used. The treatments used were Blue Complefol, in doses of 50, 100 and 150 kg / ha; Novatec Premium in doses of 50, 100 and 150 kg / ha and a conventional control (N - P - K) in doses of 180-60-150 kg / ha. The experimental design of Complete Blocks at Random was used, with seven treatments and four repetitions. The evaluated variables were subjected to the analysis of variance, using the Tukey significance test at 95% probability for comparisons of treatment means. All the necessary agricultural work was carried out in the cultivation of rice for its normal development, such as land preparation, Sowing, Irrigation, Fertilization, Weed Control, Phytosanitary Control and Harvesting. To estimate the effects of the treatments, the following variables were taken within the area of the experimental plot as plant height, number of tillers and panicles, days of flowering, length of the panicles, grains per panicles, weight of 1000 grains, grain yield and economic analysis. For the exposed results, it was determined that the soil nutrition with Complefol Azul and Novatec Premium fertilizers in the rice crop under rainfed conditions, variety Iniap FL 1480, presented positive results during its development; the conventional control treatment (N - P - K) with 180-60-150 kg / ha flourished in a longer time; the agronomic characteristics such as plant height, tillers and panicles / m2; grains and length of panicles stood out in the averages with the use of Novatec Premium, in doses of 100 kg / ha and the highest crop yield and net profit ($ 601.70) was registered with the use of Novatec Premium, in doses of 100 kg / ha, applied at 20 and 40 days after the transplant. Key words: rice, edaphic fertilization, Blue Complefol, Novatec Premium.